2016
DOI: 10.1002/14651858.cd012312
|View full text |Cite
|
Sign up to set email alerts
|

Depression rating scales for detection of major depression in people with dementia

Abstract: Depression rating scales for detection of major depression in people with dementia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 76 publications
0
3
0
Order By: Relevance
“…For example, common symptoms of dementia such as apathy can mimic depression. 54 Focusing on common symptoms of anxiety such as concentration difficulties are not likely to discriminate well between anxious and nonanxious individuals with dementia. 55 People with dementia may also present difficulties communicating or remembering their symptoms, which can further complicate the identification of relevant symptoms.…”
Section: Research Implicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, common symptoms of dementia such as apathy can mimic depression. 54 Focusing on common symptoms of anxiety such as concentration difficulties are not likely to discriminate well between anxious and nonanxious individuals with dementia. 55 People with dementia may also present difficulties communicating or remembering their symptoms, which can further complicate the identification of relevant symptoms.…”
Section: Research Implicationsmentioning
confidence: 99%
“…55 People with dementia may also present difficulties communicating or remembering their symptoms, which can further complicate the identification of relevant symptoms. Therefore, the literature suggests using an assessment tool that is designed specifically to assess depression and anxiety in dementia and derives information from multiple resources including both the person with dementia and an informant 54,56 (eg, CSDD, Rating anxiety in Dementia scale). However, this was not always the case for primary studies included in the identified reviews.…”
Section: Research Implicationsmentioning
confidence: 99%
“…The Cornell Scale for Depression in Dementia (CSDD) (Alexopoulos, Abrams, Young, & Shamoian, 1988) is a well-regarded measure that attempts to address these concerns. Even so, it remains to be agreed as to what the CSDD is measuring (Barca et al, 2015;Kirkham et al, 2016). And despite these intended improvements, measures that attempt to separate mood from other experiences in dementia are not the most widely used (van der Linde et al, 2016).…”
Section: Constrained By Mood Disordersmentioning
confidence: 99%